READING SPEED LEVEL AND COMPREHENSION IN SECOND LANGUAGE READING - M Sayid Wijaya (Jurnal Pedagogy, 2018)
Fluent readers are characterized by their ability in comprehending reading text flawlessly. They need no such a significant delay to process either word recognition or world knowledge while putting some efforts to get the gist of the text. Thus, their reading speed would increase by the time their word recognition skill improved. This also implicates their reading comprehension as well since they are skillful enough to relate what they know about the text with the text itself. However, that condition happened differently to students who joined Reading for General Purposes class. Some students who read in normal speed varied in their reading comprehension score. Students’ reading speed level must have yielded the approximate score to their speed level, moderate score. This occurrence leaded the writer to investigate if there is any correlation between students’ reading speed level and their reading comprehension. Thus, correlational research design was deployed in this research. Sample of this research were students who joined writer’s Reading for General Purposes class, 74 students. The data were collected by using tests, reading speed test and reading comprehension. After collecting the data, the writer analyzed them by using Spearman’s Rank Order Correlation to test the hypothesis. Since the result of Spearman’s rho value Sig. = .608 > α = .05, alternative hypothesis was not accepted which meant that there was no correlation between students’ reading speed level and their reading comprehension.